Antecedents Of Organizational Citizenship Behaviour - Noraini, Othman (2002)

(untitled)
The purpose of this study was to explore organizational citizenship behaviour (OCB) practices among nurses in health care institution, and to determine the relationship between demographic factors and ethical climate to OCB. Moreover, this study also tried to determine whether job satisfaction and organizational commitment moderate the relationship between ethical climate and OCB. Data were collected from 255 nurses by using stratified random sampling to ensure that every department was represented in this study. A questionnaire consisting of five measures was administered to the respondents. Two OCB instruments were used in this study to differentiate the results from using the western instrument, an instrument developed based on the context of our society. The study showed that nurses do display OCB, with high conscientiousness and sportsmanship behaviours but low helping behaviour. Demographic factors were not found to be related to OCB. The findings also revealed that job satisfaction, organizational commitment, and ethical climate were correlated to OCB. Job satisfaction and organizational commitment were shown to moderate the relationship between ethical climate and OCB.